Morphometric study of the orientation of lumbar zygapophyseal joints in a South Indian population - SP Mohanty; Madhava Pai Kanhangad; Siddarth Kamath; Asha Kamath (Journal of Orthopaedic Surgery, 2017)
Purpose: To determine the orientation of lumbar zygapophyseal joints and prevalence of facet tropism (FT) identified by computerized tomographic (CT) scans. Methods: In a cross-sectional study, 124 CT scans of patients with spinal injuries, seen between 2011and 2015, were retrospectively studied. A total of 566 uninjured motion segments were analysed. The right and left zygapophyseal joint angles (ZJAs) from L1–L2 to L5–S1 were measured on axial sections at uninjured levels. The absolute difference between the right and left ZJA was calculated to determine the prevalence and severity of FT at each level. Results: The mean ZJA (mean ± SD) at L1–L2, L2–L3, L3–L4, L4–L5 and L5–S1 was 23.55 ± 7.21, 27.97 ± 6.95, 39.47 ± 6.07, 48.32 ± 6.38 and 53.45 ± 6.67, respectively. Prevalence of FT at L1–L2, L2–L3, L3–L4, L4–L5 and L5–S1 was 22.42%, 25%, 27.19%, 47.82% and 38.5%, respectively. One-way repeated analysis of variance test showed a statistically significant difference in mean ZJA ( p < 0.05) and prevalence of FT ( p < 0.05) at different levels of the lumbar spine. Conclusions: This study confirms that ZJA is not the same at different levels of the lumbar spine. The mean ZJA progressively increases from L1–L2 to L5–S1. This could explain the greater range of movements in the lumbar spine at the lower levels. The higher prevalence of FT at L4–L5 and L5–S1 seen in this study could explain the greater incidence of disc prolapse and other degenerative disorders at these levels.